Efektivitas buku cerita bergambar berbasis budaya lokal untuk peningkatan ketrampilan membaca - Wibowo, E W; Kanzunnudin, M; Fathurohman, I (Universitas Sebelas Maret, 2023)
The background of this research is because the students' reading comprehension ability is still not in accordance with basic competencies. Reading learning media for fourth grade elementary school children makes children bored and difficult to concentrate. The teacher's creativity in making or determining learning media does not suit children's interests. The teaching materials for Local Culture-Based Picture Story Books for Learning Reading Comprehension Skills for Class IV Students are not yet available. The research method is quantitative research in the form of experimental research. Data collection techniques with tests. The research subjects were students at SDN 1 Kebloran and SDN 2 Kebloran. Data analysis used the Independent Sample test and the Paired Sample Test. The results of the effectiveness analysis on the pre test were 21.23 and the post test was 34.27. The sig value is 0.000 <0.05 so that it indicates an effect on effectiveness or in other words Ho is rejected and Ha is accepted. The conclusion of this study shows that the development of local culture-based picture story book media is effective for teaching students' reading comprehension skills.